1999
DOI: 10.1039/a902378j
|View full text |Cite
|
Sign up to set email alerts
|

Field intercomparison of diffusive samplers for measuring ammonia

Abstract: Agricultural production systems are recognised as a major source of atmospheric ammonia. Deposition of ammonia and ammonium may contribute to undesired changes in oligotrophic ecosystems. The continuous measurement of atmospheric ammonia requires expensive and sophisticated techniques and is performed only in a very restrict number of ambient air stations in Europe. Therefore, the application of passive samplers, which have the advantage of being easy to handle and cost-efficient, is useful. In the past the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 9 publications
1
29
1
Order By: Relevance
“…This coincided well with the results of Kirchner et al (1999) which reported RSD=15.2% and were valid for the same badge-type samplers with a 1-week exposure. Fur- thermore, Kirchner et al (1999) obtained smaller RSD at a longer exposure time. In the same study, an overall uncertainty of 75% for a 1-week exposure was detected.…”
Section: Ammonia Emissionssupporting
confidence: 91%
See 1 more Smart Citation
“…This coincided well with the results of Kirchner et al (1999) which reported RSD=15.2% and were valid for the same badge-type samplers with a 1-week exposure. Fur- thermore, Kirchner et al (1999) obtained smaller RSD at a longer exposure time. In the same study, an overall uncertainty of 75% for a 1-week exposure was detected.…”
Section: Ammonia Emissionssupporting
confidence: 91%
“…3). Kirchner et al (1999) reported a comparison of different passive samplers observed over 1, 2 and 4 weeks of exposure. For badge-type B samplers, the overall uncertainty varied between 25% for 2 weeks and 16% for 4 weeks of exposure.…”
Section: Relationship Between Atmospheric Nh 3 Concentration and Distmentioning
confidence: 99%
“…Passive samplers for ammonia have been analysed before for precision and accuracy (Thijsse et al, 1998;Thöni et al, 2003;Kirchner et al, 1999;Puchalski et al, 2011). None of these methods however uses the concept of a network of inexpensive sensors calibrated for each batch against a few high-quality measuring devices.…”
Section: Resultsmentioning
confidence: 99%
“…Passive sampling is a convenient method for ammonia measurements. Passive samplers (IVL, The Swedish Environmental Research Institute, Gothenburg, Sweden) were put out at approximately 1.5m above the floor for 24 hours at three times during a week (Kirchner et al, 1999). Indoor samples were compared with outdoor sampling for 1 week at different distances from the stable (1-100m).…”
Section: Hygiene Measurements In Stable Environmentmentioning
confidence: 99%